2023
DOI: 10.1039/d3an00517h
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant encapsulating N-doped carbon dots with enhanced optical properties as a selective sensor for Cr(vi) detection

Abstract: Detecting hexavalent chromium (Cr(VI)) is important for human health and environmental protection due to its high toxicity, carcinogenicity and persistence, but developing a sensor to selectively detect Cr(VI) remains challenges....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…12 However, so far this strategy has not been tried in the research of R-CDs, although a few reports have appeared on solubilization of blue-emitting CDs in surfactant micelles. 13,14 We have recently reported that when a nonionic silicone surfactant (s-PTrS) was mixed with an anionic surfactant (SDS) in water, micellar solutions with bright blue emission would be obtained. 15 Adopting these micelles as the host, in this work we report the solubilization of R-CDs obtained from pyrolysis of citric acid (CA) in formamide (FA), leading to the formation of full-color-emitting colloids covering the white light.…”
mentioning
confidence: 99%
“…12 However, so far this strategy has not been tried in the research of R-CDs, although a few reports have appeared on solubilization of blue-emitting CDs in surfactant micelles. 13,14 We have recently reported that when a nonionic silicone surfactant (s-PTrS) was mixed with an anionic surfactant (SDS) in water, micellar solutions with bright blue emission would be obtained. 15 Adopting these micelles as the host, in this work we report the solubilization of R-CDs obtained from pyrolysis of citric acid (CA) in formamide (FA), leading to the formation of full-color-emitting colloids covering the white light.…”
mentioning
confidence: 99%